Ultrasound-triggered release of ibuprofen from a chitosan-mesoporous silica composite - a novel approach for controlled drug release - Depan, Dilip; Saikia, Lakshi; Singh, Raj Pal (Macromolecular Symposia, 2010)
In this work, an attempt was made to synthesize a novel Chitosan-Mesoporous silica (CS-MS) hybrid composite to design a drug delivery system based on ultrasound triggered stimuli-responsive smart release. The in-vitro drug release properties of both the Mesoporous Silica (MS) and Chitosan (CS) hybrids were investigated. Ibuprofen (Ibu) was used as a model drug. The results from powder X-Ray diffraction (XRD) patterns, and BET N(2) adsorption isotherms exhibited that MS can accommodate drug molecules into the lumen of the channels and pores. Drug release, stimulated by temperature and pH of the release media was also investigated. We studied the Ultrasound (US) triggered release of Ibu in a simulated body fluid (pH 7.4). The results exhibited that US can be used as a non-invasive technique for drug release from polymeric materials. The enhancing effect of ultrasound on drug release is due to the Cavitation effect, without causing any significant destruction on the polymer morphology.
4th International Symposium on Macro-and Supramolecular Architectures and Materials, Dusseldorf, GERMANY, SEP 07-11, 2008
Keywords: Chitosan; drug delivery systems; ibuprofen; Mesoporous silica; Ultrasound